Latent heat transport and microlayer evaporation in nucleative boiling - Jawurek, H H (My University, 2015)
P a r t 1 o f t h i s w o r k p r o v i d e s a b r o a d o v e r v i e w a n d , w h e r e p o s s i b l e , a q u a n t i t a t i v e a s s e s s m e n t o f t h e c o m p l e x p h y s i c a l p r o c e s s e s w h i c h t o g e t h e r c o n s t i t u t e t h e m e c h a n i s m o f n u c l e a t e b o i l i n g h e a t t r a n s f e r . I t i s s h o wn t h a t u n d e r a w i d e r a n g e o f c o n d i t i o n s t h e p r i m a r y s u r f a c e - t o - 1 i q u i d h e a t f l o w s w i t h i n a n a r e a o f b u b b l e i n f l u e n c e a r c s o r e d i s t r i b u t e d a s t o m a n i f e s t t h e m s e l v e s p r e d o m i n a n t l y a s l a t e n t h e a t t r a n s p o r . t h a t i s , a s v a p o r i s a t i o n i n t o a t t a c h e d b u b b l e s . T h i s a n d r e l a t e d f i n d i n g s a r e a p p l i e d i n t h e d e r i v a t i o n o f a new p o o l b o i l i n g h e a t t r a n s f e r c o r r e l a t i o n . The c o r r e l a t i o n a l l o w s t h e p r e d i c t i o n o f b o i l i n g c u r v e s ( q / A v , r s u s AT) a t a n y p r e s s u r e p r o v i d e d t h a t o n e b o i l i n g c u r v e f ' . t h e s ame s u r f a c e - l i q u i d c o m b i n a t i o n i s . a v a i l a b l e u s a r c f r e n c e . P a r t 2 d e a l s i n g r e a t e r d e t a i l w i t h o n e o 1 t h e c o m p o n e n t p r o c e s s e s o f l a t e n t h e a t t r a n s p o r t , n a m e l y m i c r o l a y e r e v a p o r a t i o n . A l i t e r a t u r e r e v i e w r e v e a l s t h e n e e d f o r s y n c h r o n i s e d r e c o r d s o f m i c r o l a v e r g e o m e t r y v e r s u s t i m e a n d o f n o r m a l b u b b l e g r o w t h a n d d e p a r t u r e . An a p p a r a t u s d e v e l o p e d t o p r o v i d e s u c h r e c o r d s i s d e s c r i b e d . H i g h - s p e e d c i n e i n t e r f e r e n c e p h o t o g r a p h y f r o m b e n e a t h a n d t h r o u g h a t r a n s p a r e n t h e a t i n g s u r f a c e p r o v i d e d d e t a i l s o f m i c r o l a v e r g e o m e t r y a n d a n i m a g e - r e f l e c t i o n s y s t e m s y n c h r o n i s e d t h e s e r e c o r d s w i t h t h e b u b b l e p r o f i l e v i e w s . R e s u l t s a r e g i v e n f o r m e t h a n o l a n d e t h a n o l be t l i n g a t s u b a t m o s p h e r i c p r e s s u r e s a n d a t v a r i o u s h e a t • : . . x e s a n d b u l k s u b c o o l i n v c . In a l l c a s e s i t i s f o u n d t h a t m i c r o l a y e r s w e r e o f s u b - m i c r o n t h i c k n e s s , t h a t m i c r o l a y e r t h i n n i n g w a s r e s t r i c t e d t o t h e i n n e r l a y e r e d g e ( w i t h t h e t h i c k n e s s e l s e w h e r e r e m a i n i n g c o n s t a n t o r i n c r e a s i n g w i t h t i m e ) a n d t h a t t h e c o n t r i b u t i o n o f t h i s v i a i b l c e v a p o r a t i o n t o t h e t o t a l v a p o u r f l o w i n t o b u b b l e s wa s n e g l i g i b l e . T h e o b s e r v a t i o n o f t h i c k e n i n g t o w a r d s t h e o u t e r m i c r o l a y e r e d g e , h o w e v e r , d e m o n s t r a t e s t h a t a l i q u i d r e p l e n i s h m e n t f l o w o c c u r r e d s i m u l t a n e o u s l y w i t h t h e e v a p o r a t i o n p r o c e s s . T h e e f f e c t s o f s u c h r e p l e n i s h m e n t a r c i n v e s t i g a t e d b y me a n s o f a n u m e r i c a l a n a l y s i s o f m i c r o l a y c r h e a t t r a n s f e r . T h e a n a l y s i s i n d i c a t e s t h a t t h e n e t e v a p o r a t i o n f r o m t h e c o n t i n u o u s l y r e p l e n i s h e d m i c r o l a y c r s wa s a s i g n i f i c a n t c o n t r i b u t o r t o t h e t o t a l b u b b l e g r o w t h . Th e o p t i c a l r e s u l t s o f t h e p r e s e n t s t u c y a r e t h u s r e c o n c i l e d w i t h t h e d e d u c t i o n s o f p u b l i s h e d s u r f a c e - t h c r m o m c t r y s t u d i e s . T h e f o r c e s a c t i n g on t h e o b s e r v e d b u b b l e s a r c a n a l y s e d a n d a r c f o u n d t o b e c o m p a t i b l e w i t h a r e p l e n i s h m e n t m e c h a n i s m . M i c r o l a y e r i n t c r f c r o m e t r y s t u d i e s f o u n d e d on p u b l i s h e d p o r t i o n s o f t h e p r e s e n t s t u d y a r c d i s c u s s e d a n d c o n t r o v e r s i a l r e s u l t s a n a l y s e d . /
A thesis presented in fulfilment of the requirements for the degree of doctor o philosophy August 1977